Forecast from Stonehenge - Montgomery, R. A. (Choose your own adventure, 2006)
"The summer solstice is celebrated around the world, but in one place it holds particular meaning: the mysterious monument of Stonehenge. You seek a wise druid named Alastair who claims to have knowledge of the fabled missing heelstone."--Cover.